Literature Review : Implementasi Project Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis - Nurhamudin -; Bowo Sugiyarto; Puguh Karyanto (Universitas Sebelas Maret, 2025)
Education in the global era must focus on developing 21st century competencies, with critical thinking skills being one of the most important and needing to be taught explicitly. To develop critical thinking skills, the role of educators is very important in designing appropriate learning scenarios in schools. This learning scenario includes learning tools that integrate the four pillars of education established by UNESCO, namely learning to know, learning to do, learning to live together, and learning to be. yourself (learning to be). Based on these four pillars, the Project Based Learning learning model is considered very suitable for developing students' critical thinking skills. This is because in this model, students who are at the center of learning are given problems in the form of projects and they are required to solve them independently. This critical thinking ability can be improved through the application of the Project Based Learning model in learning. This research is a literature review of related articles over a period of seven years (2017-2024). The conclusion of this research shows that implementing the Project Based Learning model can be an effective strategy for improving critical thinking skills in learning. From the research results, everything indicates that the use of the Project Based Learning model in learning can improve students' critical thinking abilities.